Designing Equitable, Transparent, Community-engaged Disaster Research. (19th May 2022) - Rohlman, Diana; Samon, Samantha; Allan, Sarah; Barton, Michael; Dixon, Holly; Ghetu, Christine; Tidwell, Lane; Hoffman, Peter; Oluyomi, Abiodun; Symanski, Elaine; Bondy, Melissa; Anderson, Kim
Disaster research faces significant infrastructure challenges: regional and federal coordination, access to resources, and community collaboration. Disasters can lead to chemical exposures that potentially impact human health and cause concern in affected communities. Community-engaged research, which incorporates local knowledge and voices, is well suited for work with communities that experience impacts of environmental exposures following disasters. We present three examples of community-engaged disaster research (CEnDR) following oil spills, hurricanes, and wildfires, and their impact on long-term social, physical, and technical community infrastructure. We highlight the following CEnDR structures: researcher/community networks; convenient research tools; adaptable data collection modalities for equitable access; and return of data.